The Mitochondrial-Encoded Peptide MOTS-c Translocates to the Nucleus to Regulate Nuclear Gene Expression in Response to Metabolic Stress - Kim, Kyung Hwa; Son, Jyung Mean; Benayoun, Bérénice A.; Lee, Changhan (Cell Metabolism, 2018)
Cellular homeostasis is coordinated through communication between mitochondria and the nucleus, organelles that each possess their own genomes. Whereas the mitochondrial genome is regulated by factors encoded in the nucleus, the nuclear genome is currently not known to be actively controlled by factors encoded in the mitochondrial DNA. Here, we show that MOTS-c, a peptide encoded in the mitochondrial genome, translocates to the nucleus and regulates nuclear gene expression following metabolic stress in a 5′-adenosine monophosphate-activated protein kinase (AMPK)-dependent manner. In the nucleus, MOTS-c regulated a broad range of genes in response to glucose restriction, including those with antioxidant response elements (ARE), and interacted with ARE-regulating stress-responsive transcription factors, such as nuclear factor erythroid 2-related factor 2 (NFE2L2/NRF2). Our findings indicate that the mitochondrial and nuclear genomes co-evolved to independently encode for factors to cross-regulate each other, suggesting that mitonuclear communication is genetically integrated. The mitochondrial genome is regulated by factors encoded in the nucleus. Kim et al. now show that, reciprocally, MOTS-c, a mitochondrial-encoded peptide, can dynamically translocate to the nucleus in response to metabolic stress and regulate adaptive nuclear gene expression. Their findings suggest that mitonuclear communication is genetically integrated.
Keywords: AMP-Activated Protein Kinases; Animals; Antioxidant Response Elements; Cell Line; Cell Nucleus; Gene Expression; Gene Expression Regulation; Glucose; HEK293 Cells; Hep G2 Cells; Homeostasis; Humans; Mitochondria; Mitochondrial Proteins; NF-E2-Related Factor 2; Signal Transduction; Stress, Physiological; homeostasis; metabolic stress; mitochondria; mitochondrial DNA; mitochondrial-derived peptide (MDP); mitonuclear communication; MOTS-c; peptide; short open reading frames (sORF); stress response